2009
DOI: 10.1021/ja900036n
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer-Selective and Helix-Sense-Selective Living Block Copolymerization of Isocyanide Enantiomers Initiated by Single-Handed Helical Poly(phenyl isocyanide)s

Abstract: Rigid-rodlike right (P)- and left (M)-handed helical polyisocyanides (P-poly-L-1 and M-poly-L-1) prepared by the living polymerization of an enantiomerically pure phenyl isocyanide bearing an L-alanine pendant with a long n-decyl chain (L-1) with the mu-ethynediyl Pt-Pd catalyst were found to block copolymerize L-1 and D-1 in a highly enantiomer-selective manner while maintaining narrow molecular weight distributions. The M-poly-L-1 preferentially copolymerized L-1 over the antipode D-1 by a factor of 6.4-7.7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 111 publications
3
138
0
Order By: Relevance
“…On the other hand, the D-monomer was preferentially copolymerized over its antipode by a factor of 4.0, with the P-L-20c composed of the same L-monomer units, and the resulting polymer possessed the opposite helix sense. 90 The highresolution AFM images of block copolymers revealed that the enantiomer-selective block copolymerizations proceeded in an almost perfectly helix-sense-selective manner (Figure 11), as supported by their CD spectra, that is, the helical handedness of macroinitiators L-20c and L-20d determines the overall helical sense of block polyisocyanides, irrespective of the configuration of the monomer units (L-Ala) of initiators during block copolymerizations. As anticipated, block copolymers maintain their stiffness with a narrow molecular weight distribution and showed lyotropic smectic LC phases.…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 85%
See 1 more Smart Citation
“…On the other hand, the D-monomer was preferentially copolymerized over its antipode by a factor of 4.0, with the P-L-20c composed of the same L-monomer units, and the resulting polymer possessed the opposite helix sense. 90 The highresolution AFM images of block copolymers revealed that the enantiomer-selective block copolymerizations proceeded in an almost perfectly helix-sense-selective manner (Figure 11), as supported by their CD spectra, that is, the helical handedness of macroinitiators L-20c and L-20d determines the overall helical sense of block polyisocyanides, irrespective of the configuration of the monomer units (L-Ala) of initiators during block copolymerizations. As anticipated, block copolymers maintain their stiffness with a narrow molecular weight distribution and showed lyotropic smectic LC phases.…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 85%
“…As anticipated, block copolymers maintain their stiffness with a narrow molecular weight distribution and showed lyotropic smectic LC phases. 90 The present methodology using supramolecular self-assembly into well-defined 2D crystals on substrates provides a useful means of observing the helical structures of other complicated supramolecular helical polymers, such as an artificial double-stranded helical polymer (37) and the poly(methyl methacrylate) (PMMA) stereocomplex. Double helical 37 is composed of complementary homopolymers bearing (R)-amidine and achiral carboxylic acid units that selfassembled to form a complementary double helix with a twist-sense bias through interstrand amidinium-carboxylate salt bridges, as supported by an intense Cotton effect in the main-chain absorption region.…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
“…This backbone carries peptide functionalized side chains that are attached to every carbon stabilizing the helix through hydrogen bonding. [28][29][30] These polymers can be up to 2 mm long and exhibit a well-dened stereoregularity 31 as well as a controlled stiffness that can be tuned between persistence lengths (L P ) of 5 nm to 200 nm. 26,32 Since in principle every individual monomer can be substituted with a functional unit, a versatile synthon for the design of multivalent lamentous sDCs is easily obtained (Fig.…”
Section: 27mentioning
confidence: 99%
“…Figure 5 shows the typical AFM phase images of poly(1L m -co-1D n ) deposited on highly oriented pyrolytic graphite (HOPG) from a dilute benzene solution (0.005 mg ml À1 ), followed by benzene vapor exposure at B25 1C for 12 h. 21,22 This method is also very useful for constructing highly ordered 2D helix bundles with a controlled helicity for a dynamically racemic helical poly(phenylacetylene) 23 and helical polyisocyanides [46][47][48] on HOPG, and their helical structures were visualized by AFM. 49 Poly(1L m -co-1D n ) self-assembled into regular 2D helix bundles with a constant height (B1.6 nm), and the copolymer chains packed parallel to each other.…”
Section: Amplification Of Macromolecular Helicity In Poly(phenylacetymentioning
confidence: 99%